The Utility of the Supine-to-Stand Test as a Measure of Functional Motor Competence in Children Aged 5-9 Years - Michael J. Duncan; Chelsey Lawson; Leanne Jaye Walker; David Stodden; Emma L. J. Eyre (MDPI AG, 2017)
This study examined how supine-to-stand (STS) performance is related to process and product assessment of motor competence (MC) in children. Ninety-one children aged 5-9 years were assessed for process and product MC (10 m running speed and standing long jump) as well as process and product measures of STS. Tertiles were created for STS process and STS product scores to create 3 groups reflecting low, medium, and high STS competency. ANCOVA analysis, controlling for age, for process STS, indicated that process MC was significantly higher in children, classified as medium STS (p = 0.048) and high STS (p = 0.011) competence, and that 10 m run speed was slower for low STS compared to medium (p = 0.019) and high STS (p = 0.004). For product STS tertiles, process MC was significantly higher for children in the lowest (fastest) STS tertile compared to those in the medium highest (slowest) tertile (p = 0.01).